Biejiajian Pill Inhibits Carcinogenesis and Metastasis via the Akt/GSK-3β/Snail Signaling Pathway in Hepatocellular Carcinoma - Sun, Jialing; Chen, Weicong; Wen, Bin; Zhang, Mingjia; Sun, Haitao; Yang, Xuemei; Zhao, Wenting; La, Lei; An, Haiyan; Pang, Jie; Gao, Lei; He, Songqi (Frontiers in Pharmacology, 2021)
Hepatocellular carcinoma (HCC) is among the most usual cancers globally. In China, Biejiajian pill (BJJP), Traditional Chinese Medicine clinical prescription, is broadly utilized for the prevention and therapy of HCC. However, the mechanisms by which BJJP exerts its effects on the prevention of tumor invasion and metastasis are still largely unknown. In this study, in vitro multiple hepatic cancer cell lines and an in vivo xenograft mice model were used to validate the preventive effects and molecular mechanisms of BJJP in HCC. We established that BJJP significantly repressed the proliferation, apoptosis, metastasis and infiltration of HCC cells. Furthermore, BJJP remarkably suppressed HCC cell migration, as well as invasion via epithelial-mesenchymal transition (EMT) by modulating Snail expression, which was associated with the repression of Akt/GSK-3β/Snail signaling axis activation. In vivo HCC xenograft results indicated that BJJP delayed HCC development and efficiently inhibited lung metastasis. Taken together, BJJP was shown to be an effective therapeutic agent against HCC through repression of the Akt/GSK-3β/Snail signaling cascade and EMT.